Did Javal measure eye movements during reading? - Nicholas J. Wade; Benjamin W. Tatler (Journal of Eye Movement Research)
Louis-Émile Javal is widely credited as the first person to record eye movements in read-ing. This is so despite the fact that Javal himself never made that claim but it is perpetu-ated in contemporary text books, scientific articles and on the internet. Javal did coin the term ‘saccades’ in the context of eye movements during reading but he did not measure them. In this article we suggest that a misreading of Huey’s (1908) book on reading led to the misattribution and we attempt to dispel this myth by explaining Javal’s contribution and also clarifying who did initially describe discontinuous eye movements during reading.